An investigation into feedback and spatial relationships between banks’ share prices and sovereign bond spreads during the euro crisis - Gibson, Heather D.; Hall, Stephen G.; Petroulas, Pavlos; Tavlas, George S. (Journal of Financial Stability, 2022)
We examine (1) spillover effects between euro-area sovereigns and banking systems within national jurisdictions and (2) cross-country spillovers among ten countries during the euro-area crisis. We find that cross-country spillovers substantially amplify the doom loops between the sovereign and banking sectors. We also provide a test that supports the hypothesis that cross-country spillovers among southern-euro-area countries were of a different order from the spillovers among northern-euro-area countries. Our results also imply that, if shocks are idiosyncratic, spillover effects may help in reducing the impact for northern countries.